Cultural Hybridity in Music Accompaniment of Performing Arts Bantengan Putro Taruno Satrio Lintang Mojokerto City - Fatihah, Lauhil; Riyanto, Edi Dwi (Universitas Negeri Medan, 2024)
Bantengan is one of the performing arts that developed in several regions of East Java, one of the communities that preserve Bantengan is the Bantengan Putro Taruno Satrio Lintang Community from Mojokerto City. One of the important elements in the performance art is the music which functions as a determinant of the dynamics of the performance art game, but along with the times the music presented has undergone cultural transformation due to the process of cultural hybridity in the music. This research aims to find out the cultural hybridity contained in the music accompaniment of Bantengan Putro Taruna Satrio Lintang performance art in Mojokerto City. In this study, researchers used ethnographic methods, namely field methods in the form of case studies, namely the Bantengan Putro Taruno Satrio Lintang Community in Mojokerto City. The techniques used in this research are observation, interview, document, and triangulation techniques. In this study, researchers used an analysis method in the form of interpretative qualitative methods and used an analysis model in the form of cultural studies analysis. The result of this research is that the cultural hybridity contained in the music accompaniment of Bantengan Putro Taruna Satrio Lintang performance art is influenced by three factors, such as space, cultural agents, and time.